Pushed over the edge: insect communities at border habitats - Anderson, Magdeline Elizabeth (Kansas State University, 2023)
Increased agricultural intensification has had a profound impact on many ecological processes, including documented declines in beneficial insect abundance, richness, and their natural pest control services. With an increase in pest pressure, agrochemical use has also risen. Strategically planting perennial grassland habitat adjacent to working land, often called border cropping, is a practice that can work to counteract the negative impacts of intensification patterns and offer sustainable solutions for humans, insects, and our ecosystems long term. Border crops provide the additional shelter and food resources needed for beneficial insect survival, which boosts their abundances and diversity. Subsequently, if the beneficial insects move from the border crop into the agricultural field, they can provide natural pest control services needed to reduce pest pressure and agrochemical use. However, the effects of border crops for beneficial insects and pest control services have been mixed ranging from negative, no effect to positive effects. Mixed results have in large part been due to differences in response variables measured and different experimental approaches. Insect community patterns and spillover movement patterns within border crops and across agricultural landscapes remain relatively less well explored and must be studied more closely. It is possible that the beneficial insects are not moving between habitats, and thus have little impact on natural pest control, because the border crop’s edge might be perceived as a barrier to movement. My master’s project works to understand insect movement between agricultural fields and their adjacent habitat types. It also focuses on gaining insight into the effectiveness of border crops as a natural pest control and a conservation practice. To achieve these goals, we conducted two studies across soybean plots that were bordered by either corn or grass natural habitats. One was an observational biodiversity study and the other was an experimental mark, release, and recapture study. This two-part approach provided both a broader comprehensive view of insect dynamics and the intricate mechanistic patterns needed for scientific comprehension and agricultural management decisions. Results showed that it is likely that any edge habitat, including those created by border crops, are unique environments where they create separate communities and can be barriers to insect movement. We found that the overall pest and beneficial insect communities in soybeans were distinct from those at the edges and within the corn or grass interiors. We also found that movement between habitats was uncommon for tracked ground beetles, no matter the type of bordering habitats or type of edge. However, we also found positive indications for natural pest control with border crops. There were slightly more beneficial and less pest insects within soybean field interiors that had a border crop compared to soybean field interiors that had an adjacent corn habitat. In addition, tracked ground beetles most frequently chose to enter the soybean habitat over the grass or corn when placed at an edge. Therefore, with the implementation of various techniques, such as softening edges or using lures, border crop habitat edges could be more permeable, could promote cross habitat movement, and ultimately contribute to natural pest control.
Keywords: Beneficial insects; Border crops; Sustainable agriculture; Ground beetles; Edge habitat; Movement